1995
DOI: 10.1111/j.1699-0463.1995.tb01077.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the first notification of positive blood cultures on antibiotic therapy

Abstract: regimen being ampicillin or an ampicillin-aminoglycoside combination (295 episodes), whereas cephalosporins, thienamycin, and fluoroquinolones were seldom used (41 episodes). The ongoing antibiotic coverage was deemed appropriate in 41 8 episodes (60%), non-optimal in 90 (13%), and lacking in 186 (27%). The notification of positive blood cultures elicited changes in antibiotic therapy in 315 episodes (45%), including commencement of antibiotic therapy in 127 (18%). Thus, blood culture results have a measurable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Patients with pneumococcal bacteremia were identified in the microbiological County Bacteremia Registry, which is described in detail elsewhere (15). The registry is maintained by the Department of Clinical Microbiology at Aalborg University Hospital, which provides diagnostic bacteriology for the entire county.…”
Section: Research Design and Methods -The Study Was Conducted During mentioning
confidence: 99%
“…Patients with pneumococcal bacteremia were identified in the microbiological County Bacteremia Registry, which is described in detail elsewhere (15). The registry is maintained by the Department of Clinical Microbiology at Aalborg University Hospital, which provides diagnostic bacteriology for the entire county.…”
Section: Research Design and Methods -The Study Was Conducted During mentioning
confidence: 99%
“…Previous studies have shown that timeliness of detecting bloodstream pathogens improves antimicrobial therapy, reduces costs, and decreases length of stay and patient mortality. [3][4][5][6][7][9][10][11] Timeliness and accuracy of preliminary blood culture results represent 2 important, evidence-based quality indicators that are closely linked to clinical outcomes.…”
Section: Commentmentioning
confidence: 99%
“…Faster results reporting has been shown to be associated with lower mortality, 3 especially when combined with clinical consultation. 4,5 Other benefits of rapid reporting include improved selection of antimicrobial therapy, [6][7][8][9] lower overall health care costs, 10 and reduced length of stay. 8,11 Timely detection of bacteremia also facilitates initiation of rapid, direct methods for early identification and susceptibility testing.…”
mentioning
confidence: 99%
“…This was done through linkage to the County Bacteremia Research Database (21), which stores prospectively collected data on all blood cultures, as well as bacteriological and clinical data on all bacteremia episodes from 1997 through 2003. We considered only the first episode of bacteremia during the hospitalization for pneumonia.…”
Section: Pneumonia Outcomementioning
confidence: 99%